Europium-Subsituted Bismuth-Based Superconductors: Structural and Thermal Analysis via Chemical Sol-Gel Synthesis - Salim Abed, Firas; Abbas, Lamia K. (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
The synthesis and characterization of Bi1.7-xPb0.3EuxSr2Ca2Cu3O10+δ superconductors with Eu substitution at varying ratios were investigated to determine their structural, electrical, and thermal properties. A sol-gel technique followed by calcination was employed to prepare samples with different substitution ratios. X-ray diffraction (XRD) was used for structural analysis, electrical properties with aid of nitrogen fluid measured by electrical resistivity, thermogravimetric analysis (TGA) conducted for thermal properties , and differential scanning calorimetry (DSC) were utilized for characterization